The influence of different forms of black cumin (Nigella sativa L.) on the characteristics of sheep’s curd cheese - Voșgan, Zorica; Dumuța, Anca; Mihali, Cristina; Dippong, Thomas; Mihalescu, Lucia; Marian, Monica; Mihalescu, Beatrice (Frontiers in Sustainable Food Systems, 2024)
The influence of different forms of Nigella sativa (seeds, powder, alcoholic extract, and oil) on the traditional sheep curd was investigated by comparison with a control simple curd considering a series of sensorial, physical–chemical, and microbiological aspects. The analysis was performed on curds freshly prepared and after 10 days of refrigeration. The sensory analysis of the curds was performed using a variety of methods such as scaling method, the method of quality describing, the method of ordering by rank, “triangle” method, and “duo-trio” method. The analyzed curds were assessed and classified according to their sensory characteristics and typicality. The N. sativa supplementing of the sheep curds improved their physical–chemical characteristics by raising the fat content with 0.88–2.82% and decreasing the titratable acidity with 1.42–2.32% compared to the control curd without additive. After 10 days of refrigeration, the titratable acidity increased with 1.58–3.25% and moisture decreased (8.43–13.17%). The microbiological quality of the curd samples was influenced by the addition of black cumin in different forms, with variations in the total number of bacteria (TNB) between 4.33 and 4.39 log CFU/g compared to the control sample 5.03 log CFU/g, Enterobacteriaceae (2.53–2.58 log CFU/g) compared to the control sample 2.60 log CFU/g, and coagulase-positive staphylococci (CPS) 2.30–2.68 log CFU/g compared to the control sample 2.75 log CFU/g. After 10 days of refrigeration, the number of microorganisms decreased, TNB (4.13–4.31 log CFU/g), Enterobacteriaceae (2.34–2.53 log CFU/g), and CPS (2.02–2.55 log CFU/g), while for the control sample the values increased. The most obvious antimicrobial effect was observed in the case of the cold-pressed oil addition (1%), followed by the alcoholic extract (1%), seeds (3%), and powder (3%).